Powder synthesis, densification, microstructure and mechanical properties of Hf-based ternary boride ceramics. Issue 7 (July 2021) - Zhang, Wei; Zhang, Yan; Guo, Wei-Ming; Xu, Liang; You, Yang; Sun, Shi-Kuan; Lin, Hua-Tay; Wu, Shang-Hua
Abstract: (Hf1/3 Ti1/3 Zr1/3 )B2, (Hf1/3 Ta1/3 Zr1/3 )B2 and (Hf1/3 Ta1/3 Ti1/3 )B2 (Hf-based ternary boride, HTB) powders were synthesized by boro/carbothermal reduction method, and then densified by SPS at 2000 ℃. Results showed that HTB powders were significantly refined compared to HfB2 powder synthesized by the same process, and HTB powders doped with TaB2 combined with Ti or Zr had finer particle size (0.26−0.35 μm) than doped with TiB2 and ZrB2 (0.76 μm). Due to the fine powders and the effects of solid solution, HTB ceramics presented higher densification compared to HfB2 ceramics in the literature. The microstructure of (Hf1/3 Ti1/3 Zr1/3 )B2 ceramics exhibited a coarse microstructure around 6.62 μm, whereas (Hf1/3 Ta1/3 Zr1/3 )B2 and (Hf1/3 Ta1/3 Ti1/3 )B2 had refined microstructure, in the 1.65–2.45 μm range. (Hf1/3 Ti1/3 Zr1/3 )B2 and (Hf1/3 Ta1/3 Ti1/3 )B2 had higher hardness and fracture toughness than (Hf1/3 Ta1/3 Zr1/3 )B2 . HTB sintered ceramics with TaB2 demonstrated finer powder and microstructure, whereas HTB ceramics doped with TiB2 yielded the best mechanical properties. The microstructure and mechanical properties of HTB ceramics can be guided by selection of solid solution element.